Dinamika Perkumpulan Ikawangi di Denpasar Tahun 2009-2018 - Yosepa, Dita Juan; Putu Wahyuni, Ida Ayu; Inten Asmariati, Anak Agung (Humanis; Vol 27 No 1 (2023)DO - 10.24843/JH.2023.v27.i01.p10, 2023)
This study discusses the dynamics of the Ikawangi association as a regional association in the period 2009 to 2018. Some of the issues that will be discussed in this study are (1) How the history of Ikawangi Dewata Balo (2) How the development of Ikawangi Dewata in the period 2009 to 2018, and (3) What are the implications of Ikawangi Dewata for Banyuwangi people in Bali and non-Banyuwangi societies. This research is a historical research. The approach used in the study is social history. The historical theory used is five elements of historical theory initiated by Ida Bagus Sidemen : historical understanding, historical explanation, historical objectivity, historical causation and historical determinism. The results of this study reveal the origin and chronology of the establishment of Ikawangi Dewata as a regional-based association in Bali , the development of Ikawangi Dewata, and the implications for the Banyuwangi and non-Banyuwangi communities in Bali.